Self-Compassion and Relating It to Eating Disorder among University Students - Muwafaq Flaiyah, Ashraf (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This article aims to screen Eating Disorder Attitude among undergraduate students, as well as examining the differences in self-compassion and Eating Disorder Attitude by gender. The relation between self compassion and Eating Disorder Attitude has been investigated as well. Methods: (435) students were chosen randomly from of Baghdad University. The Arabic versions of Self compassion scale (SCS), as well as Eating Attitude Test (EAT) are used to achieve the study’s objects Results: Results showed that a quarter of the sample had symptoms of eating disorder according to the first criterion. As for the second criterion, the results indicated that just under half of the sample had met this criterion. The same thing with regard to the third criterion, the body mass index, as results showed that about half of the sample had met this criterion. Regarding to the second aim, the correlation coefficients was used between all study variables. The male data founded that one of the subscale of self-compassion (Self-Kindness subscale) was positively correlated to the first and second criteria of eating disorder. However, there were no significant correlations were founded between other variables. In other hand, the female data has different results. Where the results showed that the total score of self-compassion and Isolation subscale of self-compassion have revealed a positive correlation with only the second criterion of eating disorder.